Alkoxylation of camphene over silica-occluded tungstophosphoric acid - Castanheiro, J (2014)
Silica-occluded tungstophosphoric acid (PW-Ssg) was used as an efficient, nvironmentally friendly heterogeneous catalyst for the liquid-phase alkoxylation of camphene into their more valuable alkyl isobornyl ether, which is used as perfume and cosmetic products, in the pharmaceutical industry, as well as in the food industry. The lkoxylation of camphene with C1–C4 alcohols (methanol, ethanol, 1- propanol, 2-propanol, 1-butanol and 2-butanol) to alkyl isobornyl ether was studied in the presence of PW-Ssg (4.2% w/w) at 60–80 ◦C. Different linear and branched alcohols are compared in relation to their activity for the alkoxylation of camphene. The catalytic activity decreased with the increase of number of carbon atoms in the chain alcohol, which can be explained due to the presence of sterical hindrance and diffusion limitations inside the porous system of the catalyst. High selectivity of PW-Ssg catalyst for the alkyl isobornyl ether was observed. The effect of various parameters, such as atalysts loading, initial concentration of camphene and temperature were studied to optimise the ethoxylation of camphene. The catalytic stability of PW-Ssg in the ethoxylation of camphene was studied by performing consecutive batch runs with the same catalyst sample at the same conditions. After the third run, the catalytic activity stabilized. The catalyst can be recovered and reused without significant leaching of PW. The catalytic activity of PW-Ssg was compared with the activity of tungstophosphoric acid mmobilized on sílica by impregnation method (PW-Sim). The activity of PW-Ssg is higher than that of PW-Sim catalyst. After reaction, the PW-Sim sample lost 20% of its heteropolyacid.